The effectiveness of pre-operative care bundle on post-operative outcome among adult patients undergoing cardiac surgeries in selected hospitals - Abhilasha Valmik Gaidhani; Rupali Vishal Chaugule (Malahayati International Journal of Nursing and Health Science, 2022)
Background: Cardiovascular diseases (CVDs) are the leading cause of death globally, taking an estimated 17.9 million lives each year. CVDs are a group of disorders of the heart and blood vessels and include coronary heart disease, cerebrovascular disease, rheumatic heart disease, and other conditions. More than four out of five CVD deaths are due to heart attacks and strokes, and one-third of these deaths occur prematurely in people under 70 years of age. India has one of the highest burdens of cardiovascular disease (CVD) worldwide. The annual number of deaths from CVD in India is projected to rise from 2.26 million (1990) to 4.77 million (2020). Coronary heart disease prevalence rates in India have been estimated over the past several decades and have ranged from 1.6% to 7.4% in rural populations and from 1% to 13.2% in urban populations.Purpose: To determine the effectiveness of preoperative care packages on postoperative outcomes of CABG patients and the relationship of postoperative outcomes with clinical and demographic variables.Method: In this study, the design used was a quasi-experimental design. In this study, a simple random sampling technique was used. sample size was 40 (experimental group 20 and control group 20) Study Findings 95% of patients were diagnosed with TVD, the remaining 5% were DVD patients.Results: This shows that there is moderate with 30% and good with 70% recovery in the experimental group, while in the control group 85% is moderate, 10% is good and 5% is bad. This indicates that there is a significant difference between the postoperative outcome scores between the experimental and control groups as p<0.05Conclusion: there is a significant effect of a pre-operative care bundle in patients undergoing CABG on preventing CABG complications and increasing life expectancy.